Responsibility and Accountability in Japan after the 1990s: a Legal Perspective. Introduction to the Special Issue - Vanoverbeke, Dimitri; Kadomatsu, Narufumi (Zeitschrift für Japanisches Recht, 2011)
Introduction by the guest editors of the special issue.